Predicting the flammability of polymers from their chemical structure: An improved model based on group contributions. (8th March 2016) - Sonnier, Rodolphe; Otazaghine, Belkacem; Iftene, Fadela; Negrell, Claire; David, Ghislain; Howell, Bob A.
Abstract: A new method is proposed to calculate the flammability of polymers from their chemical structure using a Van Krevelen approach. The model is inspired from a pioneering work of Lyon which assigns one flammability contribution to each chemical group. The flammability property of the whole polymer is the sum of the contributions of chemical groups constituting the polymer. Two intrinsic properties (namely heat release capacity and total heat release) measured using pyrolysis-combustion flow calorimeter are correctly predicted for almost one hundred polymers containing contributions of only 31 chemical groups. The contributions of these groups are compared and the consistency of these values is discussed. Finally some exceptions, such as, phosphorus-containing polymers, are noted. Graphical abstract: Highlights: Flammability of polymers is calculated using a Van Krevelen approach. The contributions to HRC and THR are calculated for 31 groups. Some exceptions, such as, phosphorus-containing polymers, are identified.